2014
DOI: 10.1155/2014/762320
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Associated Encephalopathy

Abstract: Sepsis associated encephalopathy (SAE) is a common but poorly understood neurological complication of sepsis. It is characterized by diffuse brain dysfunction secondary to infection elsewhere in the body without overt CNS infection. The pathophysiology of SAE is complex and multifactorial including a number of intertwined mechanisms such as vascular damage, endothelial activation, breakdown of the blood brain barrier, altered brain signaling, brain inflammation, and apoptosis. Clinical presentation of SAE may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
172
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 123 publications
(145 reference statements)
2
172
0
14
Order By: Relevance
“…Recent studies have illustrated the pathophysiology of SAE and encephalitis involving BBB dysfunction, neuroinflammation, and apoptosis [16,23]. In this study, we observed that the inhibition of Omi/HtrA2 by UCF-101 substantially improves the sepsis-induced loss of BBB integrity, as demonstrated by improvements in Evans blue extravasation and endothelial tight junction protein expression.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 49%
See 1 more Smart Citation
“…Recent studies have illustrated the pathophysiology of SAE and encephalitis involving BBB dysfunction, neuroinflammation, and apoptosis [16,23]. In this study, we observed that the inhibition of Omi/HtrA2 by UCF-101 substantially improves the sepsis-induced loss of BBB integrity, as demonstrated by improvements in Evans blue extravasation and endothelial tight junction protein expression.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 49%
“…It may involve brain microvascular endothelial cell dysfunction, destruction of the BBB, cerebral local inflammatory cell infiltration, inflammation medium, reduced cerebral perfusion, cerebral microvascular adjustment disorder, astrocyte and neuron dysfunction, neurotransmitter disorders, mitochondrial dysfunction, apoptosis, oxidative stress, calcium disorders, and so on [1,13,15]. Compelling evidence indicates that oxidative stress, mitochondrial dysfunction, and apoptosis play critical roles in the pathogenesis of SAE [16]. Accordingly, oxidative stress may promote the pathogenesis of SAE by enhancing the expression of proinflammatory cytokines, promoting apoptosis, and/ or interfering with BBB function.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it required urgent drainage even in the presence of neuropsychiatric symptoms. 2 Wilson's disease rarely presents with acute psychosis. 3 Here the child presented with acute psychosis and was posted for a semi-emergent surgery before resolution of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Lebih dari itu, ensefalopati sepsis dikaitkan dengan prognosis yang buruk. 6,7 Salah satu biomarker yang sampai sekarang masih diteliti adalah NSE. Neuron-specific enolase adalah enzim glikolitik sitoplasma yang ditemukan pada sel neuron dan sel neuroendokrin.…”
unclassified